BOARD GAMES AND HYPERFOCUS: INCLUSION OF AUTISTIC STUDENTS IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2026)
Introduction: This article presents a pedagogical experience that integrated board games into Physical Education classes to promote the inclusion of a student with Autism Spectrum Disorder (ASD), using his hyperfocus on dinosaurs. Objective: To investigate how the use of board games, linked to the hyperfocus of a student with ASD, can contribute to inclusion in Physical Education classes by promoting engagement and the development of socio-emotional and cognitive skills. Methods: The proposal involved adaptations of traditional games, such as checkers and Adugo (Jaguar Game), mediated by psychopedagogical strategies based on Cunha’s (2017) framework: intentionality, reciprocity, meaning, and transcendence. The participants were students from the 7th grade of elementary school (aged 12 to 15), a class that included one student with ASD. Results: The experience showed that merely including elements of hyperfocus is not enough to guarantee engagement. A thoughtful pedagogical plan is essential, considering the student's specific needs. Conclusion: The results indicated benefits not only for the student with ASD but for the whole class, fostering socio-emotional and cognitive development.
Keywords: school inclusion; ASD; board games; hyperfocus; physical education